Vasculitis in a Child With the Hyper-IgM Variant of Ataxia-Telangiectasia - Meyer, Anna K.; Banks, Mindy; Nadasdy, Tibor; Clark, Jennifer J.; Zheng, Rui; Gelfand, Erwin W.; Abbott, Jordan K. (Frontiers in Pediatrics, 2019)
A subset of patients with Ataxia-Telangiectasia (A-T) have dramatically reduced levels of IgG, IgA, and IgE with retained or elevated IgM levels. Several reports suggest that these A-T patients with a “hyper-IgM phenotype” (HIgM) suffer more clinical immunologic consequences than other A-T patients. The immunopathologic mechanism driving this phenomenon is unknown, making it difficult to predict response to immunomodulatory therapy. We describe an A-T patient with HIgM who underwent tumor necrosis factor (TNF) receptor blockade for cutaneous granuloma and after several months of successful therapy developed non-malignant lymphoproliferation, cytopenia, and increased serum immunoglobulin levels. This process was subsequently followed by an immune-complex-mediated intrarenal small vessel vasculitis that led to renal failure. The vasculitis was successfully treated with rituximab and corticosteroids. This case underscores the importance of HIgM as an unfavorable prognostic indicator in A-T and highlights the complexity of immunomodulatory treatment in this population, and the potential for a successful approach tailored to the immune defect.